2015
DOI: 10.1073/pnas.1513716112
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic excitability measures track antiepileptic drug action and uncover increasing/decreasing excitability over the wake/sleep cycle

Abstract: Pathological changes in excitability of cortical tissue commonly underlie the initiation and spread of seizure activity in patients suffering from epilepsy. Accordingly, monitoring excitability and controlling its degree using antiepileptic drugs (AEDs) is of prime importance for clinical care and treatment. To date, adequate measures of excitability and action of AEDs have been difficult to identify. Recent insights into ongoing cortical activity have identified global levels of phase synchronization as measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
112
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(139 citation statements)
references
References 44 publications
8
112
1
Order By: Relevance
“…7,13 In the current study, we extended this work by demonstrating that synchronization levels correlate with the cumulative AED load in a dosagedependent manner. 7,13 In the current study, we extended this work by demonstrating that synchronization levels correlate with the cumulative AED load in a dosagedependent manner.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…7,13 In the current study, we extended this work by demonstrating that synchronization levels correlate with the cumulative AED load in a dosagedependent manner. 7,13 In the current study, we extended this work by demonstrating that synchronization levels correlate with the cumulative AED load in a dosagedependent manner.…”
Section: Discussionsupporting
confidence: 52%
“…7 To systematically explore the relationship between drug load and synchronization depending on the frequency band, we combined data from all 10 patients to calculate the average synchronization value for each AED load (Fig. 7 To systematically explore the relationship between drug load and synchronization depending on the frequency band, we combined data from all 10 patients to calculate the average synchronization value for each AED load (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, a recent study measured the amplitude of the TMS-evoked EEG response using a constant routine protocol, which helps unmasking circadian influences [28]. In line with previous sleep deprivation experiments that measured the EEG reaction to TMS [7] or intrinsic measures of cortical excitability [29], it was found that EEG responses were larger at the end as compared to the beginning of 29 hours of continuous wake [28]. The same TMS-evoked responses, however, covaried with cortisol levels and showed a significant “dip” in the evening around the so-called wake-maintenance zone, indicating a circadian effect [28].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep is hypothesized to regulate the complex organization of brain dynamics (Pearlmutter and Houghton, 2009), by keeping excitatory and inhibitory processes balanced (Huber et al, 2013). While prolonged wakefulness increases brain excitability, sleep reduces it, preventing an imbalance towards excitation that would favor runaway seizure-like activity (Meisel et al, 2013, 2015). Therefore, important pathophysiological mechanisms underlying insomnia complaints may be unveiled by studying the complex organization of brain dynamics.…”
Section: Introductionmentioning
confidence: 99%